Selection of steam turbine bypass system. (October 2019) - Sun, W; Wang, Y
Abstract: This paper introduces the functions of steam turbine bypass system for the large coal-fired power units, the types of the steam turbine bypass system, the selections of the bypass system capacity and the current design situation of domestic units. About the functional design of the steam turbine bypass system, it is designed with the following functions: starting, protecting the reheater, tracking the main steam pressure, recovering working substance, quick opening when the steam turbine trips, relief valve and fast cut back etc.. About the type of bypass system, this paper introduces the application of the bypass system for large capacity units, which can be divided into four types: the high pressure one-stage large capacity bypass system, the high and low pressure two-stage series bypass system, the tertiary bypass system and the triple-purpose valve bypass system, and the advantages and disadvantages of the design for all kinds of the bypass system. In terms of the capacity selection of the bypass system capacity, the capacity of the bypass system should be selected to match the peak-regulation capacity of the unit, while taking into account the investment and maintenance costs. In view of the current design situation of domestic units, this paper expounds the design patterns and the characteristics of the bypass system of several large thermal power units.